Karyotype analysis of spring onion, allium fistulosum L. (alliales alliaceae). - Mendoza, Joselito Trandio Piolo (1994.)
The C - metaphase count of ten cells of Allium fistulosum L. showed that the somatic chromosome number of the species was 2n = 16. Using Levan's method of chromosome classification, the chromosomes were classified into three groups; Group I chromosomes with subterminal centromeres ( 1 pair) ; Group II with submedian centromeres ( 2 pairs ); and group III with median centromeres ( 5 pairs )., The t-test for paired observations at 95 percent confidence limits showed that there is no significant difference between pairs of chromosomes in each group. Mitotic index for the species was computed at 10.35.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Spring Onions